2011
DOI: 10.1111/j.1600-0897.2011.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Foxp3 Expressing CD4+ CD25+ and CD4+ CD25 Regulatory T‐Cell Populations are Enriched in Human Early Normal Pregnancy Decidua: A Phenotypic Study of Paired Decidual and Peripheral Blood Samples

Abstract: Problem Regulatory T cells (Treg cells), a small subset of CD4+ T cells maintaining tolerance by immunosuppression, are proposed contributors to the survival of the fetal semiallograft. We investigated Treg cells in paired decidual and peripheral blood (PB) samples from healthy women in early pregnancy and PB samples from non-pregnant women. Method of study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 48 publications
3
78
0
Order By: Relevance
“…In this study, we show, to our knowledge for the first time, an accumulation of GR-MDSCs with T cell suppressive capacities at the maternal-fetal interface of healthy pregnancies but a reduced accumulation in patients with spontaneous abortions. These results parallel data from others showing an enrichment of Tregs in human decidua and an association between diminished Treg accumulation and pregnancy failure (32,34,35). Recently, reduced MDSCs in peripheral blood of patients with early miscarriage and a depletion of MDSCs leading to pregnancy failure in mice have also been shown (36,37).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this study, we show, to our knowledge for the first time, an accumulation of GR-MDSCs with T cell suppressive capacities at the maternal-fetal interface of healthy pregnancies but a reduced accumulation in patients with spontaneous abortions. These results parallel data from others showing an enrichment of Tregs in human decidua and an association between diminished Treg accumulation and pregnancy failure (32,34,35). Recently, reduced MDSCs in peripheral blood of patients with early miscarriage and a depletion of MDSCs leading to pregnancy failure in mice have also been shown (36,37).…”
Section: Discussionsupporting
confidence: 77%
“…Genetic analysis verified that most GR-MDSCs isolated from placenta were maternal cells, and immunohistochemical staining of placenta revealed that most CD66b + cells were located on the maternal side, predominantly in the intervillous space and the decidual tissue. Immunohistochemical studies on Tregs at the maternal-fetal interface showed a similar distribution of these cells in decidual stroma (34). Because CD66b staining cannot distinguish between immature GR-MDSCs with suppressive capacities and mature granulocytes, these results have to be viewed with caution.…”
Section: Discussionmentioning
confidence: 96%
“…The Treg cells are not only enriched in the decidua, they also show a more pronounced suppressive phenotype than in blood with regard to expression of, for example, Foxp3, cytotoxic T lymphocyte antigen 4 (CTLA-4), CD25, and TGF-b (Dimova et al 2011;Mjosberg et al 2010). The recruitment of decidual T cells is governed by human chorionic gonadotropin (Schumacher et al 2009) as well as by the expression of chemokine receptors and the production of corresponding ligands in the decidua, including CCR5/CCL4 (Kallikourdis et al 2007) and CCR4/CCL17 (Mjosberg et al 2010).…”
Section: Cells Of the Adaptive Immune System T Cells In The Deciduamentioning
confidence: 99%
“…The recruitment of decidual T cells is governed by human chorionic gonadotropin (Schumacher et al 2009) as well as by the expression of chemokine receptors and the production of corresponding ligands in the decidua, including CCR5/CCL4 (Kallikourdis et al 2007) and CCR4/CCL17 (Mjosberg et al 2010). In addition, Treg cells may proliferate (Mjosberg et al 2010) and mature (Dimova et al 2011) locally. An intriguing mechanism for regulating T cell traffic was recently shown; stroma cells in the decidua downregulated, by epigenetic mechanisms, their expression of chemokines CXCL9-11, known to recruit Th1 cells (Nancy et al 2012).…”
Section: Cells Of the Adaptive Immune System T Cells In The Deciduamentioning
confidence: 99%
“…In humans, CD4 + CD25 high Treg cells are enriched in the decidua, express markers of activation (CD45R0 and HLA-DR) and show a suppressive phenotype, with high expression of Foxp3 and CTLA-4 (Heikkinen et al, 2004;Tilburgs et al, 2006;Tilburgs et al, 2008;Mjosberg et al, 2010;Dimova et al, 2011). In contrast to mouse pregnancy, little is known about the specificity and the mechanisms that promote expansion of Treg cells in humans.…”
Section: Treg Cellsmentioning
confidence: 96%